An anticorrosive glass fiber mesh cloth, a preparation method and application thereof

CN122942225APending Publication Date: 2026-10-20SHIJIAZHUANG LONGCHENG FIBERGLASS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611404471.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]针对以上技术问题,本发明提供了一种抗腐蚀玻璃纤维网格布及其制备方法和应用,本发明提供的一种抗腐蚀玻璃纤维网格布及其制备方法和应用,解决了现有玻璃纤维网格布抗腐蚀性不足的技术问题

Benefits of technology

[0023]与现有技术相比,本发明提供了一种抗腐蚀玻璃纤维网格布,在玻璃纤维网格布体系中引入聚丙烯纤维,其中聚丙烯纤维本身具有优异的耐碱、耐化学腐蚀特性,可以有效提高玻璃纤维的耐腐蚀性能。然而,未改性的聚丙烯纤维与玻璃纤维之间界面相容性差,玻璃纤维网格布的耐腐蚀性不能很好的提高。本发明中聚丙烯纤维由质量比4:1.5~2.5的氨基硅烷改性聚丙烯纤维和环氧基硅烷改性聚丙烯纤维组成,其中氨基硅烷改性聚丙烯纤维可通过表面氨基基团与玻璃纤维表面基团形成作用力,有效改善界面结合力;环氧基硅烷改性聚丙烯纤维具备优异的耐酸碱腐蚀、耐水解性能,可在纤维表面形成疏水保护膜,从而阻隔腐蚀介质渗透。本发明通过两种改性聚丙烯纤维以4:1.5~2.5的质量比复配,既能保证足够的界面结合强度,又能充分发挥环氧基硅烷改性纤维的阻隔防护作用,二者协同,使得玻璃纤维网格布在碱性介质中的耐腐蚀性能得到显著提升。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention relates to the field of fiber cloth technology, and proposes a corrosion-resistant glass fiber mesh cloth, its preparation method, and its application. The preparation method of the corrosion-resistant glass fiber mesh cloth includes the following steps: S1, blending and twisting glass fiber and polypropylene fiber to obtain a blended yarn; S2, performing warping treatment on the blended yarn to obtain warp yarn; taking another blended yarn as weft yarn, and interweaving the warp and weft yarns to obtain a glass fiber mesh fabric; S3, coating the surface of the glass fiber mesh fabric with a coating slurry, and drying it to obtain the corrosion-resistant glass fiber mesh cloth; the polypropylene fiber is composed of aminosilane-modified polypropylene fiber and epoxysilane-modified polypropylene fiber in a mass ratio of 4:1.5~2.5. The corrosion-resistant glass fiber mesh cloth, its preparation method, and its application provided by this invention solve the technical problem of insufficient corrosion resistance of existing glass fiber mesh cloths.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fiber cloth technology, specifically to a corrosion-resistant glass fiber mesh cloth, its preparation method, and its application. Background Technology

[0002] Fiberglass mesh, with its high tensile strength, excellent dimensional stability, and good compatibility with substrates, is widely used in building exterior wall insulation, wall crack prevention, GRC components, waterproofing reinforcement, and industrial corrosion protection, making it a key material for ensuring the integrity and durability of engineering structures. However, during service, fiberglass mesh is often in prolonged contact with alkaline substances released from cement-based materials. In alkaline environments, hydroxide ions attack the silica-oxygen network structure of the glass fibers, causing the fibers to dissolve and their strength to drop sharply. Therefore, improving the corrosion resistance of fiberglass mesh is a prerequisite for ensuring its long-term reliable use under alkaline conditions in cement-based environments.

[0003] Currently, fiberglass mesh suffers from poor resistance to alkaline media, leading to issues such as coating peeling, fiber corrosion and embrittlement, and rapid decline in mechanical strength during practical use. This results in wall cracking, insulation layer delamination and detachment, and anti-corrosion layer failure, failing to meet the requirements for long-term corrosion protection and high durability in engineering projects. Therefore, developing fiberglass mesh with excellent corrosion resistance is of great significance for ensuring the long-term safety and durability of building structures. Summary of the Invention

[0004] To address the above technical problems, this invention provides a corrosion-resistant glass fiber mesh, its preparation method, and its application. The corrosion-resistant glass fiber mesh, its preparation method, and its application provided by this invention solve the technical problem of insufficient corrosion resistance of existing glass fiber mesh.

[0005] The specific technical solution of the present invention is as follows:

[0006] According to one aspect of the present invention, a method for preparing corrosion-resistant glass fiber mesh cloth is provided, comprising the following steps:

[0007] S1. Glass fiber and polypropylene fiber are blended and twisted to obtain blended yarn;

[0008] S2. Take the blended yarn and perform warping treatment to obtain warp yarn; take the blended yarn as weft yarn, and interweave the warp yarn and weft yarn to obtain glass fiber mesh fabric.

[0009] S3. Coating slurry is applied to the surface of the glass fiber mesh fabric and dried to obtain the corrosion-resistant glass fiber mesh fabric;

[0010] The polypropylene fiber is composed of aminosilane-modified polypropylene fiber and epoxysilane-modified polypropylene fiber in a mass ratio of 4:1.5~2.5.

[0011] In the above technical solution, the preparation method of the aminosilane modified polypropylene fiber includes the following steps: soaking polypropylene fiber in an aminosilane aqueous solution, filtering and drying to obtain the aminosilane modified polypropylene fiber.

[0012] In the above technical solution, the preparation method of the epoxy silane modified polypropylene fiber includes the following steps: soaking polypropylene fiber in an epoxy silane aqueous solution, filtering and drying to obtain the epoxy silane modified polypropylene fiber.

[0013] In the above technical solution, the coating slurry comprises the following raw materials in parts by weight: 40-60 parts of carboxylated styrene-butadiene latex, 40-60 parts of silicone-acrylic emulsion, 5-10 parts of crosslinking agent, and 5-10 parts of filler;

[0014] The filler comprises the following components in parts by weight: 5-8 parts of sodium molybdate composite kaolin, 3-5 parts of zinc stearate, and 1-3 parts of sepiolite.

[0015] In the above technical solution, the preparation method of sodium molybdate composite kaolin includes the following steps:

[0016] A1. After mixing kaolin and urea in a solvent, the mixture is filtered, washed, and dried to obtain pretreated kaolin.

[0017] A2. The pretreated kaolin is added to an aqueous solution of sodium molybdate and mixed. After filtration and drying, the sodium molybdate composite kaolin is obtained.

[0018] In the above technical solution, in step A1, the mass ratio of kaolin, urea and solvent is 10:3:0.4~0.6.

[0019] In the above technical solution, the preparation method of the coating slurry includes the following steps: mixing carboxylated styrene-butadiene latex with silicone-acrylic emulsion, adjusting the pH value to 7-9, adding crosslinking agent and filler in sequence, mixing, and then filtering to obtain the coating slurry.

[0020] According to another aspect of the present invention, the present invention also provides a mesh fabric prepared by the above-described preparation method.

[0021] According to yet another aspect of the invention, the invention also provides the application of corrosion-resistant glass fiber mesh in a cement matrix.

[0022] In the above technical solution, the application of the anti-corrosion glass fiber mesh in a cement matrix includes the following steps: cutting the anti-corrosion glass fiber mesh according to the shape of the cement matrix mold, stacking the cut anti-corrosion glass fiber mesh in the cement matrix mold according to the thickness of the cement matrix, performing hot melt molding treatment, cooling, and obtaining a cement part.

[0023] Compared with existing technologies, this invention provides a corrosion-resistant glass fiber mesh fabric by introducing polypropylene fibers into the glass fiber mesh fabric system. Polypropylene fibers themselves possess excellent alkali and chemical corrosion resistance, which can effectively improve the corrosion resistance of glass fibers. However, the interfacial compatibility between unmodified polypropylene fibers and glass fibers is poor, and the corrosion resistance of the glass fiber mesh fabric cannot be significantly improved. In this invention, the polypropylene fibers are composed of aminosilane-modified polypropylene fibers and epoxysilane-modified polypropylene fibers in a mass ratio of 4:1.5~2.5. The aminosilane-modified polypropylene fibers can effectively improve the interfacial bonding force by forming interaction forces between the amino groups on their surface and the surface groups of the glass fibers; the epoxysilane-modified polypropylene fibers possess excellent acid and alkali corrosion resistance and hydrolysis resistance, and can form a hydrophobic protective film on the fiber surface, thereby blocking the penetration of corrosive media. This invention uses a blend of two modified polypropylene fibers in a mass ratio of 4:1.5~2.5 to ensure sufficient interfacial bonding strength and fully utilize the barrier and protective effect of the epoxy silane modified fibers. The synergistic effect of the two fibers significantly improves the corrosion resistance of the glass fiber mesh in alkaline media. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of this invention more apparent, the invention is described in detail below. It should be understood that the invention is not limited to the description herein.

[0025] Fiberglass

[0026] The glass fiber used in this invention is a glass fiber known in the art that can be used in glass fiber mesh fabrics, and this invention is not limited to the glass fibers listed below. In the corrosion-resistant glass fiber mesh fabric, its preparation method, and its application, glass fiber, as the core skeleton material of the mesh fabric, possesses core advantages such as high strength, high modulus, good dimensional stability, and good temperature resistance. It can provide basic tensile strength and structural support for the blended mesh fabric, effectively improving the overall tensile and crack resistance of the mesh fabric and preventing deformation and damage under stress.

[0027] Polypropylene fiber

[0028] The polypropylene fiber used in this invention is a polypropylene fiber known in the art for use in glass fiber mesh fabrics, and this invention is not limited to the polypropylene fibers listed below. In the corrosion-resistant glass fiber mesh fabric, its preparation method, and its application, the polypropylene fiber exhibits excellent flexibility and fatigue resistance, effectively improving the defects of glass fiber's high brittleness and easy breakage, and significantly enhancing the flexibility and processing performance of the mesh fabric. Simultaneously, the polypropylene fiber itself possesses good chemical corrosion resistance and alkali resistance, effectively resisting the erosion of the alkaline environment of the cement matrix, and improving the overall durability and structural integrity of the mesh fabric in the cement matrix.

[0029] Carboxylated styrene-butadiene latex

[0030] The carboxylated styrene-butadiene latex used in this invention is a known carboxylated styrene-butadiene latex that can be used in glass fiber mesh fabrics, and this invention is not limited to the carboxylated styrene-butadiene latex listed below. For example, the carboxylated styrene-butadiene latex can be LA07 carboxylated styrene-butadiene latex or Styrofan® 7156. In the corrosion-resistant glass fiber mesh fabric, its preparation method, and its application according to this invention, the carboxylated styrene-butadiene latex possesses excellent film-forming properties, adhesion, and weather resistance. It can effectively encapsulate and solidify fibers, improving the overall structural strength and dimensional stability of the mesh fabric, avoiding problems such as loosening, fraying, and deformation. Simultaneously, it possesses good alkali resistance and corrosion resistance, and can independently impart corrosion protection to the mesh fabric base, enhancing its wear resistance and damage resistance.

[0031] silicone-acrylic emulsion

[0032] The silicone-acrylic emulsion used in this invention is a silicone-acrylic emulsion known in the art for use in glass fiber mesh fabrics, and this invention is not limited to the silicone-acrylic emulsions listed below. For example, the silicone-acrylic emulsion can be PD-6 silicone-acrylic emulsion or SD-5281 silicone-acrylic emulsion. In the anti-corrosion glass fiber mesh fabric, its preparation method, and its application according to this invention, the silicone-acrylic emulsion exhibits excellent temperature resistance, alkali resistance, and hydrophobic and impermeable properties. After film formation, it can form a dense and stable protective film, effectively blocking corrosive media such as water vapor and alkaline media from penetrating the glass fiber matrix, thus endowing the mesh fabric with excellent alkali resistance and corrosion resistance.

[0033] A method for preparing corrosion-resistant glass fiber mesh cloth

[0034] The method for preparing the corrosion-resistant glass fiber mesh of the present invention includes the following steps:

[0035] S1. Glass fiber and polypropylene fiber are blended and twisted to obtain blended yarn;

[0036] S2. Take the blended yarn and perform warping treatment to use it as the warp yarn; take another blended yarn as the weft yarn, and interweave the warp and weft yarns to obtain a glass fiber mesh fabric.

[0037] S3. Coating slurry is applied to the surface of the glass fiber mesh fabric and dried to obtain corrosion-resistant glass fiber mesh fabric;

[0038] The polypropylene fiber is composed of aminosilane-modified polypropylene fiber and epoxysilane-modified polypropylene fiber in a mass ratio of 4:1.5~2.5.

[0039] In this invention, glass fiber and polypropylene fiber are blended to obtain a mixed yarn with a fiber weight ratio of 8:1 to 2 per unit length.

[0040] In one embodiment of the present invention, the preparation method of aminosilane modified polypropylene fiber includes the following steps: soaking polypropylene fiber in an aqueous solution of aminosilane, filtering and drying to obtain aminosilane modified polypropylene fiber.

[0041] In this invention, the aminosilane is γ-aminopropyltriethoxysilane, the aminosilane aqueous solution is 1 wt% aminosilane aqueous solution, the soaking temperature is 50~60℃, and the soaking time is 2.5~3.5h.

[0042] In one embodiment of the present invention, the preparation method of epoxy silane modified polypropylene fiber includes the following steps: soaking polypropylene fiber in an aqueous solution of epoxy silane, filtering and drying to obtain epoxy silane modified polypropylene fiber.

[0043] In this invention, the epoxy silane is γ-glycidyl etheroxypropyltrimethoxysilane, the epoxy silane aqueous solution is 1 wt% epoxy silane aqueous solution, the soaking temperature is 50~60℃, and the soaking time is 2.5~3.5h.

[0044] In one embodiment of the present invention, the coating slurry comprises the following raw materials in parts by weight: 40-60 parts of carboxylated styrene-butadiene latex, 40-60 parts of silicone-acrylic emulsion, 5-10 parts of crosslinking agent, and 5-10 parts of filler.

[0045] The filler comprises the following components by weight: 5-8 parts sodium molybdate composite kaolin, 3-5 parts zinc stearate, and 1-3 parts sepiolite.

[0046] In the coating slurry, the weight parts of carboxylated styrene-butadiene latex are 40 to 60 parts, preferably 45 to 60 parts, more preferably 45 to 55 parts, and most preferably 48 to 50 parts.

[0047] In the coating slurry, the weight parts of the silicone-acrylic emulsion are 40 to 60 parts, preferably 40 to 58 parts, more preferably 45 to 55 parts, and most preferably 45 to 50 parts.

[0048] In the coating slurry, the crosslinking agent is present in 5 to 10 parts by weight, preferably 5 to 8 parts, more preferably 6 to 8 parts, and most preferably 7 to 8 parts.

[0049] In the coating slurry, the filler is 5 to 10 parts by weight, preferably 5 to 8 parts, more preferably 6 to 8 parts, and most preferably 7 to 8 parts.

[0050] In this invention, the crosslinking agent is a 30wt% glyoxal aqueous solution.

[0051] In one embodiment of the present invention, the preparation method of sodium molybdate composite kaolin includes the following steps:

[0052] A1. After mixing kaolin and urea in a solvent, the mixture is filtered, washed, and dried to obtain pretreated kaolin.

[0053] A2. Pretreated kaolin is added to an aqueous solution of sodium molybdate and mixed. After filtration and drying, sodium molybdate composite kaolin is obtained.

[0054] In this invention, the corrosion resistance of glass fiber mesh is effectively improved by adding sodium molybdate composite kaolin. Kaolin itself has excellent filling properties, high temperature resistance, and chemical stability, which can effectively fill the pores of the mesh coating, reduce the penetration channels of corrosive media, and thus improve the density and protective performance of the coating. However, kaolin is prone to agglomeration in the coating, resulting in uneven filler dispersion and weakening its corrosion resistance. After sodium molybdate composite treatment, the dispersibility of kaolin can be effectively improved. At the same time, the introduction of sodium molybdate allows kaolin to form a barrier layer in the coating, which not only fills the pores but also releases molybdate ions in the corrosive environment, forming a passivation protective film on the fiber surface, thereby significantly improving the long-term corrosion resistance of the mesh.

[0055] In this invention, the solvent is water, the mixing temperature in step A1 is 95°C, and the mixing time is 4~6h.

[0056] In this invention, the sodium molybdate aqueous solution is a 1wt% sodium molybdate aqueous solution, and the mixing temperature in step A2 is 75~85℃, and the mixing time is 2~4h.

[0057] In one embodiment of the present invention, in step A1, the mass ratio of kaolin, urea and solvent is 10:3:0.4~0.6.

[0058] In one embodiment of the present invention, the preparation method of the coating slurry includes the following steps: mixing carboxylated styrene-butadiene latex with silicone-acrylic emulsion, adjusting the pH value to 7-9, adding crosslinking agent and filler in sequence, mixing, and filtering to obtain the coating slurry.

[0059] A corrosion-resistant glass fiber mesh

[0060] The present invention also provides a mesh fabric prepared by the above preparation method.

[0061] Application of a corrosion-resistant glass fiber mesh in cement matrix

[0062] The present invention also provides the application of corrosion-resistant glass fiber mesh in cementitious matrices.

[0063] The application of a corrosion-resistant glass fiber mesh in a cement matrix includes the following steps: cutting the corrosion-resistant glass fiber mesh according to the shape of the cement matrix mold; stacking the cut corrosion-resistant glass fiber mesh in the cement matrix mold according to the thickness of the cement matrix; performing hot melt molding treatment; and cooling to obtain a cement part.

[0064] To further illustrate the present invention, the following examples will provide a detailed description. The raw materials used in the following examples and comparative examples of the present invention are all commercially available products. Specifically, the glass fiber is alkali-free glass fiber with a linear density of 1000D; the polypropylene fiber has a relative density of 0.90~0.91 and a linear density of 200D; the carboxylated styrene-butadiene latex is model LA07; the silicone-acrylic emulsion is model PD-6; the kaolin is calcined kaolin with a whiteness of 94~96 and an average particle size of 1000 mesh; and the sepiolite has an average particle size of 1250 mesh.

[0065] Example 1

[0066] By weight, 40 parts of carboxylated styrene-butadiene latex and 40 parts of silicone-acrylic emulsion were mixed evenly, and the pH value was adjusted to 7. Then, 5 parts of 30wt% glyoxal aqueous solution and 5 parts of filler were added in sequence. After mixing evenly, the mixture was filtered to obtain a coating slurry for later use. The filler consisted of 5 parts of kaolin, 3 parts of zinc stearate and 1 part of sepiolite.

[0067] By weight, 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-aminopropyltriethoxysilane and soaked at 50°C for 3.5 h. After filtration and drying, aminosilane-modified polypropylene fiber was obtained for later use. 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-glycidoxypropyltrimethoxysilane and soaked at 50°C for 3.5 h. After filtration and drying, epoxysilane-modified polypropylene fiber was obtained for later use.

[0068] Glass fiber and four strands of polypropylene fiber are blended to obtain a blended yarn with a fiber weight ratio of 8:1 per unit length. This blended yarn is then twisted to obtain a blended yarn. The blended yarn is then warped to serve as the warp yarn. Another blended yarn is used as the weft yarn. The warp and weft yarns are interwoven to obtain a glass fiber mesh fabric. A coating slurry is applied to the surface of the glass fiber mesh fabric, and it is dried at 90°C to obtain a corrosion-resistant glass fiber mesh fabric. The polypropylene fiber is composed of aminosilane-modified polypropylene fiber and epoxysilane-modified polypropylene fiber in a mass ratio of 4:1.5.

[0069] Example 2

[0070] By weight, 50 parts of carboxylated styrene-butadiene latex and 50 parts of silicone-acrylic emulsion were mixed evenly, and the pH value was adjusted to 8. Then, 8 parts of 30wt% glyoxal aqueous solution and 8 parts of filler were added in sequence. After mixing evenly, the mixture was filtered to obtain a coating slurry for later use. The filler consisted of 7 parts of kaolin, 4 parts of zinc stearate and 2 parts of sepiolite.

[0071] By weight, 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-aminopropyltriethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, aminosilane-modified polypropylene fiber was obtained for later use. 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-glycidoxypropyltrimethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, epoxysilane-modified polypropylene fiber was obtained for later use.

[0072] Glass fiber and four strands of polypropylene fiber are blended to obtain a mixed yarn with a fiber weight ratio of 8:1.5 per unit length. The yarn is then twisted to obtain a blended yarn. The blended yarn is then warped to serve as the warp yarn. Another blended yarn is used as the weft yarn. The warp and weft yarns are interwoven to obtain a glass fiber mesh fabric. A coating slurry is applied to the surface of the glass fiber mesh fabric, and it is dried at 110℃ to obtain a corrosion-resistant glass fiber mesh fabric. The polypropylene fiber is composed of aminosilane-modified polypropylene fiber and epoxysilane-modified polypropylene fiber with a mass ratio of 4:1.5.

[0073] Example 3

[0074] By weight, 60 parts of carboxylated styrene-butadiene latex and 60 parts of silicone-acrylic emulsion were mixed evenly, and the pH value was adjusted to 9. Then, 10 parts of 30wt% glyoxal aqueous solution and 10 parts of filler were added in sequence. After mixing evenly, the mixture was filtered to obtain a coating slurry for later use. The filler consisted of 8 parts of kaolin, 5 parts of zinc stearate and 3 parts of sepiolite.

[0075] By weight, 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-aminopropyltriethoxysilane and soaked at 60°C for 2.5 h. After filtration and drying, aminosilane-modified polypropylene fiber was obtained for later use. 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-glycidoxypropyltrimethoxysilane and soaked at 60°C for 2.5 h. After filtration and drying, epoxysilane-modified polypropylene fiber was obtained for later use.

[0076] Glass fiber and four strands of polypropylene fiber are blended to obtain a blended yarn with a fiber weight ratio of 8:2 per unit length. This blended yarn is then twisted to obtain a blended yarn. The blended yarn is then warped to serve as the warp yarn. Another blended yarn is used as the weft yarn. The warp and weft yarns are interwoven to obtain a glass fiber mesh fabric. A coating slurry is applied to the surface of the glass fiber mesh fabric, and it is dried at 130℃ to obtain a corrosion-resistant glass fiber mesh fabric. The polypropylene fiber is composed of aminosilane-modified polypropylene fiber and epoxysilane-modified polypropylene fiber with a mass ratio of 4:1.5.

[0077] Example 4

[0078] By weight, 40 parts of carboxylated styrene-butadiene latex and 40 parts of silicone-acrylic emulsion were mixed evenly, and the pH value was adjusted to 7. Then, 5 parts of 30wt% glyoxal aqueous solution and 8 parts of filler were added in sequence. After mixing evenly, the mixture was filtered to obtain a coating slurry for later use. The filler consisted of 5 parts of kaolin, 3 parts of zinc stearate and 1 part of sepiolite.

[0079] By weight, 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-aminopropyltriethoxysilane and soaked at 50°C for 3.5 h. After filtration and drying, aminosilane-modified polypropylene fiber was obtained for later use. 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-glycidoxypropyltrimethoxysilane and soaked at 50°C for 3.5 h. After filtration and drying, epoxysilane-modified polypropylene fiber was obtained for later use.

[0080] Glass fiber and four strands of polypropylene fiber are blended to obtain a blended yarn with a fiber weight ratio of 8:1 per unit length. This blended yarn is then twisted to obtain a blended yarn. The blended yarn is then warped to serve as the warp yarn. Another blended yarn is used as the weft yarn. The warp and weft yarns are interwoven to obtain a glass fiber mesh fabric. A coating slurry is applied to the surface of the glass fiber mesh fabric, and it is dried at 110℃ to obtain a corrosion-resistant glass fiber mesh fabric. The polypropylene fiber is composed of aminosilane-modified polypropylene fiber and epoxysilane-modified polypropylene fiber in a mass ratio of 4:2.

[0081] Example 5

[0082] By weight, 40 parts of carboxylated styrene-butadiene latex and 40 parts of silicone-acrylic emulsion were mixed evenly, and the pH value was adjusted to 7. Then, 5 parts of 30wt% glyoxal aqueous solution and 8 parts of filler were added in sequence. After mixing evenly, the mixture was filtered to obtain a coating slurry for later use. The filler consisted of 5 parts of kaolin, 3 parts of zinc stearate and 1 part of sepiolite.

[0083] By weight, 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-aminopropyltriethoxysilane and soaked at 50°C for 3.5 h. After filtration and drying, aminosilane-modified polypropylene fiber was obtained for later use. 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-glycidoxypropyltrimethoxysilane and soaked at 50°C for 3.5 h. After filtration and drying, epoxysilane-modified polypropylene fiber was obtained for later use.

[0084] Glass fiber and four strands of polypropylene fiber are blended to obtain a blended yarn with a fiber weight ratio of 8:1 per unit length. This blended yarn is then twisted to obtain a blended yarn. The blended yarn is then warped to serve as the warp yarn. Another blended yarn is used as the weft yarn. The warp and weft yarns are interwoven to obtain a glass fiber mesh fabric. A coating slurry is applied to the surface of the glass fiber mesh fabric, and it is dried at 110℃ to obtain a corrosion-resistant glass fiber mesh fabric. The polypropylene fiber is composed of aminosilane-modified polypropylene fiber and epoxysilane-modified polypropylene fiber with a mass ratio of 4:2.5.

[0085] Example 6

[0086] Kaolin and urea were added to water (the mass ratio of kaolin, urea and solvent was 10:3:0.5) and mixed at 95°C for 5 hours. After filtration, washing and drying, pretreated kaolin was obtained. 20 parts of pretreated kaolin were added to 80 parts of 1wt% sodium molybdate aqueous solution and mixed at 80°C for 3 hours. After filtration and drying at 120°C for 3 hours, sodium molybdate composite kaolin was obtained.

[0087] By weight, 50 parts of carboxylated styrene-butadiene latex and 50 parts of silicone-acrylic emulsion were mixed evenly, and the pH value was adjusted to 8. Then, 8 parts of 30wt% glyoxal aqueous solution and 8 parts of filler were added in sequence. After mixing evenly, the coating slurry was obtained by filtration. The filler consisted of 7 parts of sodium molybdate composite kaolin, 4 parts of zinc stearate and 2 parts of sepiolite.

[0088] By weight, 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-aminopropyltriethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, aminosilane-modified polypropylene fiber was obtained for later use. 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-glycidoxypropyltrimethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, epoxysilane-modified polypropylene fiber was obtained for later use.

[0089] Glass fiber and four strands of polypropylene fiber are blended to obtain a mixed yarn with a fiber weight ratio of 8:1.5 per unit length. The yarn is then twisted to obtain a blended yarn. The blended yarn is then warped to serve as the warp yarn. Another blended yarn is used as the weft yarn. The warp and weft yarns are interwoven to obtain a glass fiber mesh fabric. A coating slurry is applied to the surface of the glass fiber mesh fabric, and it is dried at 110℃ to obtain a corrosion-resistant glass fiber mesh fabric. The polypropylene fiber is composed of aminosilane-modified polypropylene fiber and epoxysilane-modified polypropylene fiber with a mass ratio of 4:1.5.

[0090] Example 7

[0091] Kaolin and urea were added to water (the mass ratio of kaolin, urea and solvent was 10:3:0.5) and mixed at 95°C for 5 hours. After filtration, washing and drying, pretreated kaolin was obtained. 20 parts of pretreated kaolin were added to 90 parts of 1wt% sodium molybdate aqueous solution and mixed at 80°C for 3 hours. After filtration and drying at 120°C for 3 hours, sodium molybdate composite kaolin was obtained.

[0092] By weight, 50 parts of carboxylated styrene-butadiene latex and 50 parts of silicone-acrylic emulsion were mixed evenly, and the pH value was adjusted to 8. Then, 8 parts of 30wt% glyoxal aqueous solution and 8 parts of filler were added in sequence. After mixing evenly, the coating slurry was obtained by filtration. The filler consisted of 7 parts of sodium molybdate composite kaolin, 4 parts of zinc stearate and 2 parts of sepiolite.

[0093] By weight, 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-aminopropyltriethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, aminosilane-modified polypropylene fiber was obtained for later use. 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-glycidoxypropyltrimethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, epoxysilane-modified polypropylene fiber was obtained for later use.

[0094] Glass fiber and four strands of polypropylene fiber are blended to obtain a mixed yarn with a fiber weight ratio of 8:1.5 per unit length. The yarn is then twisted to obtain a blended yarn. The blended yarn is then warped to serve as the warp yarn. Another blended yarn is used as the weft yarn. The warp and weft yarns are interwoven to obtain a glass fiber mesh fabric. A coating slurry is applied to the surface of the glass fiber mesh fabric, and it is dried at 110℃ to obtain a corrosion-resistant glass fiber mesh fabric. The polypropylene fiber is composed of aminosilane-modified polypropylene fiber and epoxysilane-modified polypropylene fiber with a mass ratio of 4:1.5.

[0095] Example 8

[0096] Kaolin and urea were added to water (the mass ratio of kaolin, urea and solvent was 10:3:0.5) and mixed at 95°C for 5 hours. After filtration, washing and drying, pretreated kaolin was obtained. 20 parts of pretreated kaolin were added to 100 parts of 1wt% sodium molybdate aqueous solution and mixed at 80°C for 3 hours. After filtration and drying at 120°C for 3 hours, sodium molybdate composite kaolin was obtained.

[0097] By weight, 50 parts of carboxylated styrene-butadiene latex and 50 parts of silicone-acrylic emulsion were mixed evenly, and the pH value was adjusted to 8. Then, 8 parts of 30wt% glyoxal aqueous solution and 8 parts of filler were added in sequence. After mixing evenly, the coating slurry was obtained by filtration. The filler consisted of 7 parts of sodium molybdate composite kaolin, 4 parts of zinc stearate and 2 parts of sepiolite.

[0098] By weight, 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-aminopropyltriethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, aminosilane-modified polypropylene fiber was obtained for later use. 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-glycidoxypropyltrimethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, epoxysilane-modified polypropylene fiber was obtained for later use.

[0099] Glass fiber and four strands of polypropylene fiber are blended to obtain a mixed yarn with a fiber weight ratio of 8:1.5 per unit length. The yarn is then twisted to obtain a blended yarn. The blended yarn is then warped to serve as the warp yarn. Another blended yarn is used as the weft yarn. The warp and weft yarns are interwoven to obtain a glass fiber mesh fabric. A coating slurry is applied to the surface of the glass fiber mesh fabric, and it is dried at 110℃ to obtain a corrosion-resistant glass fiber mesh fabric. The polypropylene fiber is composed of aminosilane-modified polypropylene fiber and epoxysilane-modified polypropylene fiber with a mass ratio of 4:1.5.

[0100] Example 9

[0101] Kaolin and urea were uniformly mixed at a mass ratio of 20:0.9 to obtain a kaolin mixture;

[0102] By weight, 50 parts of carboxylated styrene-butadiene latex and 50 parts of silicone-acrylic emulsion were mixed evenly, and the pH value was adjusted to 8. Then, 8 parts of 30wt% glyoxal aqueous solution and 8 parts of filler were added in sequence. After mixing evenly, the mixture was filtered to obtain a coating slurry for later use. The filler consisted of 7 parts of kaolin mixture, 4 parts of zinc stearate and 2 parts of sepiolite.

[0103] By weight, 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-aminopropyltriethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, aminosilane-modified polypropylene fiber was obtained for later use. 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-glycidoxypropyltrimethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, epoxysilane-modified polypropylene fiber was obtained for later use.

[0104] Glass fiber and four strands of polypropylene fiber are blended to obtain a mixed yarn with a fiber weight ratio of 8:1.5 per unit length. The yarn is then twisted to obtain a blended yarn. The blended yarn is then warped to serve as the warp yarn. Another blended yarn is used as the weft yarn. The warp and weft yarns are interwoven to obtain a glass fiber mesh fabric. A coating slurry is applied to the surface of the glass fiber mesh fabric, and it is dried at 110℃ to obtain a corrosion-resistant glass fiber mesh fabric. The polypropylene fiber is composed of aminosilane-modified polypropylene fiber and epoxysilane-modified polypropylene fiber with a mass ratio of 4:1.5.

[0105] Comparative Example 1

[0106] By weight, 50 parts of carboxylated styrene-butadiene latex and 50 parts of silicone-acrylic emulsion were mixed evenly, and the pH value was adjusted to 8. Then, 8 parts of 30wt% glyoxal aqueous solution and 8 parts of filler were added in sequence. After mixing evenly, the mixture was filtered to obtain a coating slurry for later use. The filler consisted of 7 parts of kaolin, 4 parts of zinc stearate and 2 parts of sepiolite.

[0107] By weight, 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-aminopropyltriethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, aminosilane-modified polypropylene fiber was obtained for later use. 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-glycidoxypropyltrimethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, epoxysilane-modified polypropylene fiber was obtained for later use.

[0108] Glass fiber and four strands of polypropylene fiber are blended to obtain a blended yarn with a fiber weight ratio of 8:1.5 per unit length. The yarn is then twisted to obtain a blended yarn. The blended yarn is then warped to serve as the warp yarn. Another blended yarn is used as the weft yarn. The warp and weft yarns are interwoven to obtain a glass fiber mesh fabric. A coating slurry is applied to the surface of the glass fiber mesh fabric, and it is dried at 110°C to obtain a corrosion-resistant glass fiber mesh fabric. The polypropylene fiber is an aminosilane-modified polypropylene fiber.

[0109] Comparative Example 2

[0110] By weight, 50 parts of carboxylated styrene-butadiene latex and 50 parts of silicone-acrylic emulsion were mixed evenly, and the pH value was adjusted to 8. Then, 8 parts of 30wt% glyoxal aqueous solution and 8 parts of filler were added in sequence. After mixing evenly, the mixture was filtered to obtain a coating slurry for later use. The filler consisted of 7 parts of kaolin, 4 parts of zinc stearate and 2 parts of sepiolite.

[0111] By weight, 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-aminopropyltriethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, aminosilane-modified polypropylene fiber was obtained for later use. 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-glycidoxypropyltrimethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, epoxysilane-modified polypropylene fiber was obtained for later use.

[0112] Glass fiber and four strands of polypropylene fiber are blended to obtain a blended yarn with a fiber weight ratio of 8:1.5 per unit length. The yarn is then twisted to obtain a blended yarn. The blended yarn is then warped to serve as the warp yarn. Another blended yarn is used as the weft yarn. The warp and weft yarns are interwoven to obtain a glass fiber mesh fabric. A coating slurry is applied to the surface of the glass fiber mesh fabric, and it is dried at 110°C to obtain a corrosion-resistant glass fiber mesh fabric. The polypropylene fiber is an epoxy silane modified polypropylene fiber.

[0113] Comparative Example 3

[0114] By weight, 50 parts of carboxylated styrene-butadiene latex and 50 parts of silicone-acrylic emulsion were mixed evenly, and the pH value was adjusted to 8. Then, 8 parts of 30wt% glyoxal aqueous solution and 8 parts of filler were added in sequence. After mixing evenly, the mixture was filtered to obtain a coating slurry for later use. The filler consisted of 7 parts of kaolin, 4 parts of zinc stearate and 2 parts of sepiolite.

[0115] By weight, 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-aminopropyltriethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, aminosilane-modified polypropylene fiber was obtained for later use. 5 parts of polypropylene fiber were added to 25 parts of 1 wt% aqueous solution of γ-glycidoxypropyltrimethoxysilane and soaked at 55°C for 3 hours. After filtration and drying, epoxysilane-modified polypropylene fiber was obtained for later use.

[0116] Glass fiber and four strands of polypropylene fiber are blended to obtain a blended yarn with a fiber weight ratio of 8:1.5 per unit length. The yarn is then twisted to obtain a blended yarn. The blended yarn is then warped to serve as the warp yarn. Another blended yarn is used as the weft yarn. The warp and weft yarns are interwoven to obtain a glass fiber mesh fabric. A coating slurry is applied to the surface of the glass fiber mesh fabric, and it is dried at 110°C to obtain a corrosion-resistant glass fiber mesh fabric, wherein the polypropylene fiber is unmodified polypropylene fiber.

[0117] Performance testing

[0118] The corrosion-resistant glass fiber mesh fabric was tested according to the test method specified in GB / T 20102-2006 "Test Method for Alkali Resistance of Glass Fiber Mesh Fabric - Sodium Hydroxide Solution Immersion Method".

[0119] The performance of each embodiment and comparative example after testing is shown in Table 1.

[0120] Table 1 Performance test results of Examples 1-9 and Comparative Examples 1-3

[0121] Group Retention rate of meridional tensile strength at break (%) Retention rate of latitudinal tensile breaking strength (%) Example 1 79.3 82.1 Example 2 79.8 82.6 Example 3 79.6 82.3 Example 4 80.0 83.0 Example 5 79.5 82.7 Example 6 84.7 88.0 Example 7 85.1 88.5 Example 8 84.5 87.8 Example 9 80.2 83.2 Comparative Example 1 75.2 77.5 Comparative Example 2 74.5 77.0 Comparative Example 3 72.8 76.1

[0122] As shown in Table 1, the retention rates of warp and weft tensile breaking strength in Examples 1-5 were higher than those in Comparative Examples 1-3, indicating that when polypropylene fibers are composed of aminosilane-modified polypropylene fibers and epoxysilane-modified polypropylene fibers in a mass ratio of 4:1.5-2.5, the corrosion resistance of glass fiber mesh can be effectively improved.

[0123] The retention rates of warp and weft tensile breaking strength in Examples 6-8 were higher than those in Examples 2 and 9, indicating that when the kaolin is sodium molybdate composite kaolin, the corrosion resistance of the glass fiber mesh can be further improved.

[0124] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a corrosion-resistant glass fiber mesh, characterized in that, Includes the following steps: S1. Glass fiber and polypropylene fiber are blended and twisted to obtain blended yarn; S2. Take the blended yarn and perform warping treatment to obtain warp yarn; take the blended yarn as weft yarn, and interweave the warp yarn and weft yarn to obtain glass fiber mesh fabric. S3. Coating slurry is applied to the surface of the glass fiber mesh fabric and dried to obtain the corrosion-resistant glass fiber mesh fabric; The polypropylene fiber is composed of aminosilane-modified polypropylene fiber and epoxysilane-modified polypropylene fiber in a mass ratio of 4:1.5~2.

5.

2. The method for preparing a corrosion-resistant glass fiber mesh according to claim 1, characterized in that, The preparation method of the aminosilane-modified polypropylene fiber includes the following steps: soaking polypropylene fiber in an aqueous solution of aminosilane, filtering and drying to obtain the aminosilane-modified polypropylene fiber.

3. The method for preparing a corrosion-resistant glass fiber mesh according to claim 1, characterized in that, The preparation method of the epoxy silane modified polypropylene fiber includes the following steps: soaking polypropylene fiber in an aqueous solution of epoxy silane, filtering and drying to obtain the epoxy silane modified polypropylene fiber.

4. The method for preparing a corrosion-resistant glass fiber mesh according to claim 1, characterized in that, The coating slurry comprises the following raw materials in parts by weight: 40-60 parts of carboxylated styrene-butadiene latex, 40-60 parts of silicone-acrylic emulsion, 5-10 parts of crosslinking agent, and 5-10 parts of filler; The filler comprises the following components in parts by weight: 5-8 parts of sodium molybdate composite kaolin, 3-5 parts of zinc stearate, and 1-3 parts of sepiolite.

5. The method for preparing a corrosion-resistant glass fiber mesh according to claim 4, characterized in that, The preparation method of the sodium molybdate composite kaolin includes the following steps: A1. After mixing kaolin and urea in a solvent, the mixture is filtered, washed, and dried to obtain pretreated kaolin. A2. The pretreated kaolin is added to an aqueous solution of sodium molybdate and mixed. After filtration and drying, the sodium molybdate composite kaolin is obtained.

6. The method for preparing a corrosion-resistant glass fiber mesh according to claim 5, characterized in that, In step A1, the mass ratio of kaolin, urea and solvent is 10:3:0.4~0.

6.

7. The method for preparing a corrosion-resistant glass fiber mesh according to claim 1, characterized in that, The preparation method of the coating slurry includes the following steps: mixing carboxylated styrene-butadiene latex with silicone-acrylic emulsion, adjusting the pH value to 7-9, adding crosslinking agent and filler in sequence, mixing, and filtering to obtain the coating slurry.

8. A corrosion-resistant glass fiber mesh, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 7.

9. The application of the corrosion-resistant glass fiber mesh fabric as described in claim 8 in a cement matrix.

10. The application of the corrosion-resistant glass fiber mesh according to claim 9 in a cement matrix, characterized in that, The process includes the following steps: cutting the anti-corrosion fiberglass mesh according to the shape of the cement matrix mold; stacking the cut anti-corrosion fiberglass mesh in the cement matrix mold according to the thickness of the cement matrix; performing hot melt molding treatment; and cooling to obtain the cement part.